2019
DOI: 10.1093/biolre/ioz162
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I prevents hypoxia-inducible factor-1 alpha-dependent G1/S arrest by activating cyclin E/cyclin-dependent kinase2 via the phoshatidylinositol-3 kinase/AKT/forkhead box O1/Cdkn1b pathway in porcine granulosa cells†

Abstract: As the follicle develops, the thickening of the granulosa compartment leads to progressively deficient supply of oxygen in granulosa cells (GCs) due to the growing distances from the follicular vessels. These conditions are believed to cause hypoxia in GCs during folliculogenesis. Upon hypoxic conditions, several types of mammalian cells have been reported to undergo cell cycle arrest. However, it remains unclear whether hypoxia exerts any impact on cell cycle progression of GCs. On the other hand, although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 55 publications
1
14
1
Order By: Relevance
“…Luteinization is the process by which the follicular granulosa and theca cells are transformed into luteal cells. It begins in the developing follicle, whose interior is under hypoxic conditions [7][8][9][10].…”
Section: Luteinizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Luteinization is the process by which the follicular granulosa and theca cells are transformed into luteal cells. It begins in the developing follicle, whose interior is under hypoxic conditions [7][8][9][10].…”
Section: Luteinizationmentioning
confidence: 99%
“…Luteinization is the process by which the follicular granulosa and theca cells are transformed into luteal cells. It begins in the developing follicle, whose interior is under hypoxic conditions [ 7 , 8 , 9 , 10 ]. Moderate hypoxia, such as the hypoxia in the peri-ovulatory follicles, has been shown to stimulate P4 production in granulosa cells (GCs) [ 11 , 12 , 13 ].…”
Section: Luteinizationmentioning
confidence: 99%
“…As one type of stress, hypoxia has been suggested to induce cell cycle arrest at G0/G1 phase and to block G1-to-S transition (Gardner et al, 2001). According to our previous studies, chemical-simulated hypoxia in primary cultured GCs could arrest cells at the G1/S boundary (Li et al, 2020). However, current evidence does not indicate whether and how real hypoxia acts on regulating GC cell cycle in vivo.…”
Section: Introductionmentioning
confidence: 84%
“…1I). Among the top 20 enriched pathways, we paid greater attention to FOXO1 signalling, because our previous studies suggested FOXO1 to be a crucial mediator of the stress response in ovarian GCs (Li et al, 2020;Shen et al, 2018Shen et al, , 2017Shen et al, , 2012Shen et al, , 2014, and FOXO1 is the only FOXO family member present in our transcriptomic data.…”
Section: Cell Cycle Progression Of Ovarian Gcs Might Be Regulated By ...mentioning
confidence: 99%
See 1 more Smart Citation